DISCRIMINANT MODELS OF THE LIKELIHOOD AND CHARACTERISTICS OF MULTIPLE SCLEROSIS PROGRESSION IN UKRAINIAN MEN DEPENDING ON BODY SIZE PARAMETERS - Gunas, M.М.; Moskovko, G.S.; Rutska, I.A.; Galunko, G.M.; Antoniuk, T.V. (World of Medicine and Biology, 2024)
In young Ukrainian men, based on the characteristics of body size, reliable discriminant models were built, which allow with high probability (correctness of the classification matrix 100 % of cases, Wilks' Lambda statistics=0.051, p
Keywords: nervous diseases; multiple sclerosis; anthropometric indicators; discriminant models; practically healthy and sick men